2010
DOI: 10.1371/journal.ppat.1001138
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Inhibition at the Clinical Phase of Prion Disease Reduces Neurodegeneration, Improves Behavioral Alterations and Increases Animal Survival

Abstract: Prion diseases are fatal neurodegenerative disorders characterized by a long pre-symptomatic phase followed by rapid and progressive clinical phase. Although rare in humans, the unconventional infectious nature of the disease raises the potential for an epidemic. Unfortunately, no treatment is currently available. The hallmark event in prion diseases is the accumulation of a misfolded and infectious form of the prion protein (PrPSc). Previous reports have shown that PrPSc induces endoplasmic reticulum stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 64 publications
5
63
0
1
Order By: Relevance
“…17,18 Rapamycin did extend survival to a moderate extent only under certain experimental conditions. 19,25 In our study, the early administration at 20 d.p.i of FK506 prolonged the survival of Fukuoka-1-infected mice. In contrast, the late administration (60 d.p.i.)…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…17,18 Rapamycin did extend survival to a moderate extent only under certain experimental conditions. 19,25 In our study, the early administration at 20 d.p.i of FK506 prolonged the survival of Fukuoka-1-infected mice. In contrast, the late administration (60 d.p.i.)…”
Section: Discussionsupporting
confidence: 51%
“…Mukherjee et al have recently reported that FK506 suppressed the function of calcineurin leading to the reduction of prion-induced neurodegeneration, 25 and concluded that FK506 treatment does not alter the extent of accumulation of PRNP Sc , astrocytosis or microglial activation at the terminal stage of the disease. These findings are consistent with our observation that no significant difference was observed between the brains of FK506-treated mice and those of control animals at the terminal stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, targeting of the anti-apoptotic protein BCL-2 to the ER membrane could decrease PrP Sc toxicity and cells infected with prions were more susceptible to ER stress-induced apoptosis [148,155,156]. At the molecular level PrP Sc conversion may affect ER calcium homeostasis [157,155], triggering ER stress [154], which may culminate in cellular death [159].…”
Section: Prion-related Disordersmentioning
confidence: 99%
“…Moreover, conditional knockout of Prnp expression halted disease progression and recovered certain brain functions even after disease onset (Mallucci et al 2002(Mallucci et al , 2003 (Karapetyan et al 2013). For example, the compound tacrolimus has been shown to reduce both membrane and intracellular PrP C levels by a nontranscriptional mechanism (Karapetyan et al 2013), to suppress neurodegenerative processes in prioninfected animals by acting as a calcineurin inhibitor (Mukherjee et al 2010), and to activate autophagy in both prion-infected cells and animals (Nakagaki et al 2013).…”
Section: Insights From Therapeutic Studies For Prp Prion Diseasementioning
confidence: 99%